Nucleotide sequence of the tra YALE region from IncFV plasmid pED208. - Finlay, B B (1986)
The pED208 plasmid is a 90-kilobase conjugative plasmid which is the derepressed form of Fo lac plasmid (IncFV). A 3.3-kilobase HindIII-PstI fragment from the pED208 plasmid was cloned and sequenced and was found to contain four open reading frames which were highly homologous to the traA, traL, traE, and traY gene products of the F plasmid. The pED208 traA propilin protein was 119 amino acids in length, consisting of a leader sequence of 55 amino acids and a mature pilin subunit of 64 residues. The leader sequence contained a hydrophobic region followed by a classic signal peptidase cleavage site (Ala-Ser-Ala-55). F and pED208 pilin proteins shared 27 conserved residues and had similar predicted secondary structures. The pED208 traA and traL genes were separated by a single base pair, and no ribosome binding site preceded the traL gene. The pED208 traY gene contained an IS2 insertion element in orientation II 180 nucleotides (60 residues) upstream of the traY stop codon. This insertion of IS2 resulted in a predicted fusion peptide of 69 residues for traY which may provide the observed traY activity. Since IS2 is absent in the wild-type plasmid, Fo lac, derepression and concomitant multipiliation may be due to the insertion of IS2 providing constitutive expression of the pED208 tra operon.